E-government website development : future trends and strategic models - Downey, Ed, 1945-; Ekstrom, Carl D.; Jones, Matthew A., 1975- (Hershey, PA : Information Science Reference, 2011)
'This book provides fundamental clues about the direction forward in electronic government needed to achieve even greater value from websites and assist the continuing transformation of governmental interaction with citizens'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Internet in public administration; Government Web sites; Electronic government information; Political participation -- Technological innovations